Understanding the Birth, Quality and Collapse of Democratic Regimes through Movement-Party Interactions - Mosca, Lorenzo (PARTECIPAZIONE E CONFLITTO, 2023)
This article provides a discussion of Sid Tarrow's "Movements and Parties. Critical Connections in American Political Development". First, it discusses the concept of movementization of parties. Second, it focuses on the main linkage and relational mechanisms that define the interaction between parties and movements. Next, it introduces the comparative part of Tarrow's book highlighting the role that movements play in the processes of democratic anchoring and de-anchoring. Eventually, it critically reviews the concept of hybridity by attempting to uncover the constitutive mechanisms of the process of movementization and its empirical referents in recent U.S. history.